THE BASIC WAYS OF TEACHING VOCABULARY FOR EFL STUDENTS - Khamrayeva Nafisabonu Iskandar qizi (Western European Studies, 2024)
As we know, vocabulary is an essential part of language that has a great role in teaching of English language. Teaching vocabulary is a vital part of any English language course. Many teachers are concerned about how to teach vocabulary. New words have to be introduced in such a way as to capture the students’ attention and place the words in their memories. Students need to be aware of techniques for memorising large amounts of new vocabulary in order to progress in their language learning.
Keywords: active; passive vocabulary; word association